Web-Based Tuition Payment Application System at SDIT Fidarussalam South Cikarang - Susilo, Arif; Purnama, Lukman (Lentera Ilmu Nusantara, 2025)
This study aims to design and implement a web-based tuition payment system at SDIT Fidarussalam, Cikarang Selatan. The research was motivated by the manual payment recording process that often caused errors, duplication, and potential data loss. To address these issues, the study applied the waterfall development model, which includes stages of requirement analysis, system design, coding, testing, and maintenance. Data collection was conducted through observation, interviews, and literature study. The system was developed using PHP and MySQL, while UML diagrams were employed as design tools. The results show that the system enables efficient, accurate, and structured data management. Key features include student data entry, payment processing, receipt generation, and reporting. Black-box testing confirmed that all functional requirements were successfully met, and the system operated as expected. The implementation of the web-based tuition payment system significantly improves administrative efficiency and accuracy compared to the previous manual method. It reduces human error, prevents data duplication, and minimizes the risk of data loss. Moreover, it streamlines payment processes and facilitates better record management. In conclusion, this research demonstrates that adopting a web-based application can enhance school administration by integrating technology into financial management. The system provides a reliable solution for managing tuition payments while ensuring data security and supporting decision-making through comprehensive reporting features.